2021
DOI: 10.3390/horticulturae7110469
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Proline and L-Cysteine Alleviates Internal Browning and Maintains Eating Quality of Cold Stored Flat ‘Maleki’ Peach Fruits

Abstract: The postharvest life of flat peach fruit is limited by the appearance of chilling injury symptoms, especially internal browning. In this study, impacts of the exogenous application of proline (0, 5, 10, and 15 mM) and L-cysteine (0, 0.2, 0.4 and 0.6%) on attenuating chilling injury of flat peach fruit were evaluated all over the cold storage. The results demonstrated that the fruits treated with 15 mM proline and 0.4 % L-cysteine showed lower levels of internal browning and these treatments prevented the exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 67 publications
(100 reference statements)
8
14
0
Order By: Relevance
“…Post-harvest chitosan coating has shown to be effective in enhancing activities of CAT, SOD and POD in guava [65] and fresh in-hull pistachio fruit [80]. These results are in agreement with previous studies that have reported the beneficial effect of proline in increasing ROS scavenging enzyme activities as found in rose [81], citrus [32] and flat peach [82]. In the present study, when compared with uncoated fruit, the CTS-and Pro-treated strawberries showed lower H 2 O 2 accumulation and O 2 −2 production as a result of higher SOD and CAT activity during cold storage.…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 91%
“…Post-harvest chitosan coating has shown to be effective in enhancing activities of CAT, SOD and POD in guava [65] and fresh in-hull pistachio fruit [80]. These results are in agreement with previous studies that have reported the beneficial effect of proline in increasing ROS scavenging enzyme activities as found in rose [81], citrus [32] and flat peach [82]. In the present study, when compared with uncoated fruit, the CTS-and Pro-treated strawberries showed lower H 2 O 2 accumulation and O 2 −2 production as a result of higher SOD and CAT activity during cold storage.…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 91%
“…2 showed that preharvest application of salicylic acid, calcium acetate and their combination decreased fruit TSS, total sugars and peel anthocyanin content. The results of this study are in consistent with Kassem et al (2011), Awad, (2013), El-Shazly et al (2013 and Gohari et al (2021). Preharvest application of calcium and salicylic acid before harvest increased fruit acidity, peel chlorophyll a, b and decreased fruit TSS of "Florida king" peaches (Ali et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The positive role of salicylic acid, calcium acetate and proline on reducing weight loss could be attributed to its influence on stabilizing the structure of membranes, enhancing antioxidant system, postponing the senescence process, decreased electrolyte leakage (Kumar et al, 2010, Awad, 2013, Gang et al, 2014, Aly et al, 2019and Mohammad et al, 2019. Exogenous application of proline at 15 mM on "Flat peach" fruit during the cold storage showed higher activity of phenylalanine ammonia lyase (PAL) and conversely lower activity of polyphenol oxidase (PPO), which led to a higher accumulation of total phenols and flavonoids which reflects on peel anthocyanin contents (Gohari et al, 2021).…”
Section: Data In Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Together with proline, sugars also protect photosystems against peroxidation under water deficit stress [139]. Besides these, a reduction in electrolytic leakage, H 2 O 2, and MDA was confined in certain horticulture crops when treated with 0.4% L-cysteine and 15 mM proline under chilling stress [213]. The mechanism is that L-cysteine and proline decrease the permeability of the membrane as well as lowers fatty acid peroxidation at membranal regions.…”
Section: Ros Scavenging By Non-enzymatic Antioxidantsmentioning
confidence: 99%